Comparison of antibody persistency through one year between one-dose and two-dose regimens of Ad5-nCoV vaccine for COVID-19 - Jia-Lu Feng; Wen-Juan Wang; Peng-Fei Jin; Hui Zheng; Lai-Run Jin; Xin Xia; Xiao-Yin Zhang; Zhuo-Pei Li; Jing-Xin Li; Feng-Cai Zhu (Taylor & Francis Group, 2023)
This post-hoc analysis compared the receptor-binding domain (RBD)-specific and pseudovirus neutralizing antibodies against the wild-type SARS-CoV-2 strain elicited by one or two doses (56-d interval) of Ad5-nCoV vaccine regimen (NCT04341389 and NCT04566770). Both trials had low-dose and high-dose groups. Propensity score matching was used to adjust the baseline between one- and two-dose regimens. To predict the decrease in antibody titers 1 y after vaccination, half-lives of RBD-binding antibodies and pseudovirus neutralizing antibodies were computed. We obtained 34 and 29 pairs of participants in the low- and high-dose groups based on the propensity score matching. The two-dose regimen of Ad5-nCoV increased the peaking level of neutralizing antibodies compared to the one-dose regimen at day 28, but the responses of the neutralizing antibodies were not consistent with those of the RBD antibodies. Half-lives of the RBD-binding antibodies in the two-dose Ad5-nCoV regimen (202-209 days) were longer than those in the one-dose regimen (136-137 d); half-lives of the pseudovirus neutralizing antibody in the one-dose Ad5-nCoV regimen (177 d) were longer than those in the two-dose regimen (116-131 d). The predicted positive rates of RBD-binding antibodies in the one-dose regimen (34.1%-38.3%) would be lower than those in the two-dose Ad5-nCoV regimen (67.0%-84.0%), while the positive rates of pseudovirus neutralizing antibodies in the one-dose regimen (65.4%-66.7%) would be higher than those in the two-dose regimen (48.3%-58.0%). The two-dose Ad5-nCoV regimen with a 56-d interval had no effect on the persistence of neutralizing antibodies but slowed decay trend of RBD-binding antibodies.